Effects of dietary fermented sugar kelp (Saccharina latissima) on intestinal histology, antioxidant capacity, and immune-related biomarkers of post-smolt Atlantic salmon (Salmo salar) - Sahar Sartipiyarahmadi; Ingvild Lunderød Øverbø; Benjamin Costas; Lourenço Ramos-Pinto; Nina S. Liland; Harald Sveier; Silje Steinsund; Tom Johnny Hansen; Øivind Strand; Jan Vidar Jakobsen; Antony J. Prabhu Philip; Sofie C. Remø (Fish & Shellfish Immunology, 2026)

Physical-mechanical properties of fucoidan-alginate composite hydrogels - Joachim S. Kjesbu; Tore Kristoffer Wæhre; Wenche I. Strand; Catherine T. Nordgård; Berit L. Strand; Finn L. Aachmann (Carbohydrate Polymers, 2026)

Weak influence of light and time of day on transcriptional response to SAV3 infection in Atlantic salmon (Salmo salar) smolts - Therese Solberg; Chandra S. Ravuri; Mattis Jayme van Dalum; Jo Espen Tau Strand; David G. Hazlerigg; Eva Stina Edholm; Alexander C. West (Fish & Shellfish Immunology, 2026)

Genome‐Wide Population Structure in a Marine Keystone Species, the European Flat Oyster ( Ostrea edulis ) - Homère J. Alves Monteiro; Dorte Bekkevold; George Pacheco; Stein Mortensen; Runyang Nicolas Lou; Nina O. Therkildsen; Arnaud Tanguy; Chloé Robert; Pierre De Wit; Dorte Meldrup; Ane T. Laugen; Philine S. E. zu Ermgassen; et al. (Molecular Ecology, 2025)
Ostrea edulis, the European flat oyster, was once a widespread economically and ecologically important marine species, but has suffered dramatic declines over the past two centuries. Consequently, there has been a surge in European restoration efforts, many of which focus on restocking as a conservation measure. In this study, we used whole‐genome sequencing (WGS) data to investigate the population structure, demographic history, and patterns of local adaptation of O. edulis across its natural distribution with increased sampling densities at Scandinavian localities. Results revealed seven distinct genetic clusters, including previously undescribed complex population structure in Norway, and evidence for introgression between genetic clusters in Scandinavia. We detected large structural variants (SVs) on three pseudo‐chromosomes. These megabase long regions were characterised by strong linkage disequilibrium and clear geographical differentiation, suggestive of chromosomal inversions potentially associated with local adaptation. The results indicated that genomic traces of past translocations of non‐native O. edulis were still present in some individuals, but overall, we found limited evidence of major impacts of translocations on the scale of contemporary population structure. Our findings highlight the importance of considering population structure and signatures of selection in the design of effective conservation strategies to preserve and restore wild native European flat oyster populations, and we provide direct knowledge safeguarding sustainable mitigation actions in this important species.

Trend analyses of persistent organic pollutants in human milk from first-time mothers in Norway between 2002 and 2021 - Kristina R. Nermo; Kjersti S. Bakken; Jan L. Lyche; Anuschka Polder; Aina Jansen; Siri Kaldenbach; Gabrielle Haddad-Weiser; Tor A. Strand; Merete Å. Eggesbø (International Journal of Hygiene and Environmental Health, 2025)

Reflections on the past, present, and potential futures of knowledge hierarchies in ocean biodiversity governance research - Holly J. Niner; David Wilson; Kelly Hoareau; Mia Strand; Jennifer Whittingham; Dylan McGarry; Bolanle Erinosho; Sulley Ibrahim; Sirkka Tshiningayamwe; Senia Febrica; Alana Malinde S. N. Lancaster; Milica Prokic (Frontiers in Marine Science, 2024)
Governance of the ocean and its biodiversity is deeply entangled within social, political and cultural histories. The evolution of marine science has been subject to similar influences, and we (the authors) consider these factors to create, embed and reinforce knowledge hierarchies in ocean governance processes and associated research that set societal patterns of prioritisation and exclusion. Such knowledge hierarchies have constructed dominant Western-oriented knowledge systems as ‘rational’ and ‘objective’ approaches to environmental governance in contrast to non-Western knowledge systems and have led to a dominance of natural (normal) sciences over centralised biodiversity governance. The extraction and incorporation of traditional knowledge into the Western-oriented scientific canon through myriad historical and contemporary processes in ocean biodiversity governance often reproduce knowledge hierarchies, do not benefit knowledge holders and are often considered incomplete, inappropriate or absent. As we address current ocean biodiversity and conservation challenges, researchers must be aware of the history of knowledge extraction, impositions and assumptions within their fields. Researchers must also actively acknowledge and address these histories in their work to avoid marginalisation and support ethical, empathetic, and rigorous knowledge production that meets the needs of society. In this paper, through a development of the concept of knowledge hierarchies, we explore case studies of research diverse in geography and discipline ranging from action research in Namibia, the application of arts-based methodologies in legal proceedings to research focused at an international level, and the concept of ocean literacies, all of which are located under the umbrella of a project specifically targeting transformative ocean governance. It becomes evident that knowledge hierarchies are multi-layered, perpetuating, and often reproduced even when attempting to address hierarchies through such methods as the integration or ‘bringing together’ of diverse knowledge systems. Effective change will therefore require sensitive and multi-faceted approaches to knowledge hierarchies, including processes of embracing discomfort, which will be important to work with, as well as through. While there will be continued tensions between hierarchies, it is a sine qua non that researchers need to build a commitment to understanding where powers lie, rather than ignoring such imbalances or, similarly, by idealising approaches.

Two invasive Hieracium species’ potential distributions within the Greater Yellowstone Ecosystem were defined using invasion susceptibility models and habitat typing - Christie H. Guetling; Lisa C. Jones; Eva K. Strand; Don W. Morishita; Julia Piaskowski; Timothy S. Prather (Biological Invasions, 2023)
Invasive Hieracium plant species are invading the Greater Yellowstone Ecosystem. The potential distribution of orange hawkweed ( Hieracium aurantiacum) and meadow hawkweed ( Hieracium caespitosum) were estimated using habitat susceptibility models to assist land managers’ management of these invasive plants. The objectives of this study were to: (1) develop models describing susceptibility of ecosystems to hawkweed invasion, (2) identify indicator species of orange hawkweed and meadow hawkweed, (3) determine habitat types where these invasive hawkweeds might occur, and (4) create habitat susceptibility maps for management planning and ground surveys. Models were developed using a Mahalanobis distance similarity technique from remotely sensed biotic and abiotic variables, as well as known location data for orange and meadow hawkweed. Ground validation was conducted to assess model weaknesses and subsequent model modification. Indicator plant species were identified as surrogates to determine the likelihood of hawkweed presence during ground survey. Transect data collected from areas susceptible to invasion also were used to determine habitat types where hawkweed might occur. The best model included eight variables: north–south aspect, east–west aspect, slope, NDVI, NDWI, blue spectral band, green spectral band, and precipitation. High susceptibility (65 + % likelihood of suitable habitat) consisted of 66,000 ha for meadow hawkweed and 35,000 ha for orange hawkweed, 5.0% and 2.7% of the study area, respectively. Meadow hawkweed and orange hawkweed had seven and three indicator plant species, respectively. Predicted hawkweed habitat susceptibility encompassed nine habitat types, ranging from xeric sagebrush steppe to wet forests and they overlapped except at the xeric habitat type. Habitat susceptibility models save costs and allow survey prioritization to those areas most susceptible to invasion.

Tradeoffs and synergies in wetland multifunctionality: A scaling issue - P.A. Hambäck; L. Dawson; P. Geranmayeh; J. Jarsjö; I. Kačergytė; M. Peacock; D. Collentine; G. Destouni; M. Futter; G. Hugelius; S. Hedman; S. Jonsson; et al. (Science of The Total Environment, 2023)

Sequential extraction and fractionation of four polysaccharides from cultivated brown algae Saccharina latissima and Alaria esculenta - Paulina S. Birgersson; Maren Oftebro; Wenche I. Strand; Olav A. Aarstad; Gerd Inger Sætrom; Håvard Sletta; Øystein Arlov; Finn Lillelund Aachmann (Algal Research, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

The Potential of Kelp Saccharina japonica in Shielding Pacific Oyster Crassostrea gigas From Elevated Seawater pCO2 Stress - Zengjie Jiang; Weiwei Jiang; Samuel P. S. Rastrick; Xiaoqin Wang; Jinghui Fang; Meirong Du; Yaping Gao; Yuze Mao; Øivind Strand; Jianguang Fang (Frontiers in Marine Science, 2022)
Ocean acidification (OA) caused by elevated atmospheric CO 2 concentration is predicted to have negative impacts on marine bivalves in aquaculture. However, to date, most of our knowledge is derived from short-term laboratory-based experiments, which are difficult to scale to real-world production. Therefore, field experiments, such as this study, are critical for improving ecological relevance. Due to the ability of seaweed to absorb dissolved carbon dioxide from the surrounding seawater through photosynthesis, seaweed has gained theoretical attention as a potential partner of bivalves in integrated aquaculture to help mitigate the adverse effects of OA. Consequently, this study investigates the impact of elevated p CO 2 on the physiological responses of the Pacific oyster Crassostrea gigas in the presence and absence of kelp ( Saccharina japonica ) using in situ mesocosms. For 30 days, mesocosms were exposed to six treatments, consisting of two p CO 2 treatments (500 and 900 μatm) combined with three biotic treatments (oyster alone, kelp alone, and integrated kelp and oyster aquaculture). Results showed that the clearance rate (CR) and scope for growth (SfG) of C. gigas were significantly reduced by elevated p CO 2 , whereas respiration rates (MO 2 ) and ammonium excretion rates (ER) were significantly increased. However, food absorption efficiency (AE) was not significantly affected by elevated p CO 2 . The presence of S. japonica changed the daytime pH NBS of experimental units by ~0.16 units in the elevated p CO 2 treatment. As a consequence, CR and SfG significantly increased and MO 2 and ER decreased compared to C. gigas exposed to elevated p CO 2 without S. japonica. These findings indicate that the presence of S. japonica in integrated aquaculture may help shield C. gigas from the negative effects of elevated seawater p CO 2 .

Disrupting the disruptors: the consequences of mutations in mobile elements for ecologically important life history traits - Matthew T. Rutter; April M. Bisner; Clare Kohler; Keyaira Morgan; Olivia Musselman; Julia Pickel; Jerica Tan; Yuki Yamasaki; Jay Willson; Hilary S. Callahan; Allan E. Strand; Courtney J. Murren (Evolutionary Ecology, 2020)

When and where plant‐soil feedback may promote plant coexistence: a meta‐analysis - Kerri M. Crawford; Jonathan T. Bauer; Liza S. Comita; Maarten B. Eppinga; Daniel J. Johnson; Scott A. Mangan; Simon A. Queenborough; Allan E. Strand; Katharine N. Suding; James Umbanhowar; James D. Bever (Ecology Letters, 2019)
Plant‐soil feedback (PSF) theory provides a powerful framework for understanding plant dynamics by integrating growth assays into predictions of whether soil communities stabilise plant–plant interactions. However, we lack a comprehensive view of the likelihood of feedback‐driven coexistence, partly because of a failure to analyse pairwise PSF, the metric directly linked to plant species coexistence. Here, we determine the relative importance of plant evolutionary history, traits, and environmental factors for coexistence through PSF using a meta‐analysis of 1038 pairwise PSF measures. Consistent with eco‐evolutionary predictions, feedback is more likely to mediate coexistence for pairs of plant species (1) associating with similar guilds of mycorrhizal fungi, (2) of increasing phylogenetic distance, and (3) interacting with native microbes. We also found evidence for a primary role of pathogens in feedback‐mediated coexistence. By combining results over several independent studies, our results confirm that PSF may play a key role in plant species coexistence, species invasion, and the phylogenetic diversification of plant communities.

Nemertean taxonomy—Implementing changes in the higher ranks, dismissing Anopla and Enopla - Malin Strand; Jon Norenburg; José E. Alfaya; Fernando Ángel Fernández‐Álvarez; Håkan S Andersson; Sonia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Gregorio Bigatti; Irina Cherneva; Alexey Chernyshev; Brian M. Chung; et al. (Zoologica Scripta, 2019)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Duff Distribution Influences Fire Severity and Post-Fire Vegetation Recovery in Sagebrush Steppe - Nathan I. Weiner; Eva K. Strand; Stephen C. Bunting; Alistair M. S. Smith (Ecosystems, 2016)

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Long-term monitoring of western aspen—lessons learned - E. K. Strand; S. C. Bunting; L. A. Starcevich; M. T. Nahorniak; G. Dicus; L. K. Garrett (Environmental Monitoring and Assessment, 2015)

Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women - S. Ellefsen; O. Vikmoen; G. Slettaløkken; J. E. Whist; H. Nygaard; I. Hollan; I. Rauk; G. Vegge; T. A. Strand; T. Raastad; B. R. Rønnestad (European Journal of Applied Physiology, 2014)

Voluntary responses and limits of tolerance to pressure reduction and swimbladder expansion in farmed Atlantic cod - Tore S. Kristiansen; Lars H. Stien; Jan Erik Fosseidengen; Espen Strand; Jon-Erik Juell (Aquaculture International, 2011)

Massive settlements of the Pacific oyster, Crassostrea gigas, in Scandinavia - Anna-Lisa Wrange; Johanna Valero; Lisbeth S. Harkestad; Øivind Strand; Susanne Lindegarth; Helle Torp Christensen; Per Dolmer; Per Sand Kristensen; Stein Mortensen (Biological Invasions, 2010)

Massive settlements of the Pacific oyster, Crassostrea gigas, in Scandinavia - Anna-Lisa Wrange; Johanna Valero; Lisbeth S. Harkestad; Øivind Strand; Susanne Lindegarth; Helle Torp Christensen; Per Dolmer; Per Sand Kristensen; Stein Mortensen (Biological Invasions, 2010)

Mycorrhizal and rhizomorph dynamics in a loblolly pine forest during 5 years of free‐air‐CO 2 ‐enrichment - S. G. PRITCHARD; A. E. STRAND; M. L. McCORMACK; M. A. DAVIS; R. OREN (Global Change Biology, 2008)
Soil fungi couple plant and ecosystem resource demands to pools of soil resources. Research on these organisms is needed to predict how rising atmospheric CO 2 will influence forest ecosystem processes and soil carbon (C) sequestration potential. We examined the influence of free‐air‐CO 2 ‐enrichment (FACE) on mycorrhizal and extraradical rhizomorph dynamics over a 5‐year period in a loblolly pine forest using minirhizotrons. Standing crop of mycorrhizal root tips varied greatly spatially and through time. Summed across all years, CO 2 enrichment increased mycorrhizal root tip production by 194% in deep soil (15–30 cm) but did not influence mycorrhizal production in shallow soil (0–15 cm). Production and mortality of soil rhizomorph length was 27% and 25% greater in CO 2 ‐enriched plots compared with controls over a 5‐year period beginning in January of 2000 and running through autumn 2004. Effects of atmospheric CO 2 enrichment on longevity of mycorrhizal root tips and rhizomorphs varied with soil depth (mycorrhizae and rhizomorphs) and with diameter (rhizomorphs). For instance, survival of mycorrhizal tips was reduced in CO 2 ‐enriched plots in deep soil (15–30 cm depth) but was increased in shallower soil (0–15 cm). Rhizomorph turnover was accelerated in shallow soil but effects on survivorship in deep soil varied according to diameter. A drought in 2002 coupled with loss of leaf area to an ice storm late in 2002 were followed by reductions in rhizomorph and mycorrhizal production, increases in mortality, and decreases in standing crop during 2003 and 2004. These effects tended to be more severe in CO 2 ‐enriched plots. Positive effects of atmospheric CO 2 enrichment on mycorrhizal fungi, primarily observed in deeper soil, are probably contributing to the prolonged stimulation of NPP by CO 2 enrichment at the Duke FACE study site.

The Lyngen Gabbro: the lower crust of an Ordovician Incipient Arc - Astri J. S. Kvassnes; Anita Hetland Strand; Heidi Moen-Eikeland; Rolf Birger Pedersen (Contributions to Mineralogy and Petrology, 2004)

Estimating the patch size of larval fishes during colonization on coral reefs - D. Lecchini; V. Dufour; J. Carleton; S. Strand; R. Galzin (Journal of Fish Biology, 2004)
Fish larvae were sampled daily over a period of 14 days using six crest nets spaced at 200 m intervals on a coral reef on the west coast of Moorea Island, French Polynesia, to estimate the extent to which ichthyonekton arriving at one location reflected ichthyonekton arriving at neighbouring areas. Each night, the six crest nets were colonized by larval fishes from the same location.

Anaerobic transformation of 1,1,1-trichloroethane by municipal digester sludge - Chun Chen; Bhasker S. Ballapragada; Jaakko A. Puhakka; Stuart E. Strand; John F. Ferguson (Biodegradation, 1999)

Synthesis of theoretical and empirical experiences from nutrient and cyprinid reductions in Lake Ringsjön - E. Bergman; L.-A. Hansson; A. Persson; J. Strand; P. Romare; M. Enell; W. Granéli; J. M. Svensson; S. F. Hamrin; G. Cronberg; G. Andersson; E. Bergstrand (Hydrobiologia, 1999)

Mechanisms regulating abundance of submerged vegetation in shallow eutrophic lakes - S. E. B. Weisner; John A. Strand; Håkan Sandsten (Oecologia, 1997)

Oxygen and nitrate reduction kinetics of a nonflocculating strain of Zoogloea ramigera - S. E. Strand; A. J. McDonnell; R. F. Unz (Antonie van Leeuwenhoek, 1988)

Stimulation of oviposition and successful rearing ofTelenomus heliothidis [Hym.: Scelionidae] on nonhosts by use of a host-recognition kairomone - M. R. Strand; S. B. Vinson (BioControl, 1982)

Sectional notes - Carl H. Metzger; W. B. Ward; H. L. Cochran; J. B. R. Dickey; A. B. Strand; W. H. Friend; H. H. Zimmerley; G. S. Ralston (American Journal of Potato Research, 1939)